ALKALINE PHOSPHATASE ACTIVITY IN OVARIES OF SOME CLUPEOIDS - Rao, T Appa (Indian Journal of Fisheries, 2011)
The alkaline phosphatase activity .has been determaned in the three differentstages of growth of the ovary of Stolepliorux lieterolobus, Stolephorus commersonii,Thryssa mystax. Tliryssa sctirostris, Thryssa vitrirostiis and Sardinella jussieu. Thephosphatase activity rises to a peak in the- maturing stage (Stage tl) and declinesin the mature stage (Stage IM) to about the same level or slightly higher levelthan in the immature stage